1995
DOI: 10.1111/j.1600-0536.1995.tb00674.x
|View full text |Cite
|
Sign up to set email alerts
|

The 12‐year prognosis of hand dermatosis in 896 Finnish farmers

Abstract: In all, 896 Finnish farmers (305 men and 587 women), representing 77% of those reporting hand or forearm dermatosis in a questionnaire survey in 1979, were asked again about their dermatosis and current work in 1991. More than 50% of the study population had left farming since 1979. In 1991, 26% of men and 21% of women had a current dermatosis on the hands or forearms, and altogether, 44% of men and 39% of women reported a hand dermatosis within the past 12 months. Significant determinants of persistent hand d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
2
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 18 publications
6
45
2
4
Order By: Relevance
“…17,30,38,40 The prognosis has been reported to be worse for ACD than ICD in earlier studies, 17,39,41-44 but our results do not support this. We previously reported that patients with ICD at baseline had a higher proportion of severe OHE than did patients with ACD 30 ; however, at 1-year follow-up we could no longer detect any significant differences between the 2 diagnostic groups.…”
Section: Poor Prognosis and Diagnosescontrasting
confidence: 57%
See 1 more Smart Citation
“…17,30,38,40 The prognosis has been reported to be worse for ACD than ICD in earlier studies, 17,39,41-44 but our results do not support this. We previously reported that patients with ICD at baseline had a higher proportion of severe OHE than did patients with ACD 30 ; however, at 1-year follow-up we could no longer detect any significant differences between the 2 diagnostic groups.…”
Section: Poor Prognosis and Diagnosescontrasting
confidence: 57%
“…8 As in previous studies, 17,38 we found no effect of sex on the prognosis, although contradictory findings have been published. 7,8,39 Poor socioeconomic status has been shown to affect outcome adversely in many chronic disorders.…”
Section: Poor Prognosis and Age Sex And Socioeconomic Statussupporting
confidence: 42%
“…In einer bei finnischen Bauern durchgeführten Studie wurde eine Persistenz des Handekzems bei 44% der Männer und 39% der Frauen festgestellt [41]. Meding et al.…”
Section: Epidemiologie Des Handekzemsunclassified
“…In einer in der Automobilindustrie durchgeführten prospektiven Kohortenstudie mit einer durchschnittlichen Nachbeobachtungszeit von 13,3 Jahren persistierte bzw. rezidivierte das Handekzem während der Nachbeobachtungszeit bei 40% derjenigen Beschäftigten, die während der Ausbildungszeit ein Handekzem entwickelt hatten [3]; 18% entwickelten ein Handekzem nach Ausbildungsende.In einer bei finnischen Bauern durchgeführten Studie wurde eine Persistenz des Handekzems bei 44% der Männer und 39% der Frauen festgestellt [41]. Meding et al.…”
unclassified
“…Männern und in 39% bei Frauen festgestellt[49].Meding et al [38] identifizierten in einer Übersichtsarbeit 17 Follow-up-Studien über Handekzeme, die mindestens 100 Fälle eingeschlossen hatten. Sie fanden in ungefähr der Hälfte der eingeschlossenen Studien ein Persistieren des Handekzems in 60% und mehr.…”
unclassified